PENGARUH MODEL PEMBELAJARAN JIGSAW TERHADAP HASIL BELAJAR FIKIH PESERTA DIDIK KELAS XI MAN SOLOK - Sartika Sartika; Martin Kustati; Bashori Bashori (JIP: Jurnal Ilmu Pendidikan, 2025)
This research was motivated by the low learning outcomes of student , their lack of active participation during the learning process, and the use of conventional teaching models that tend to cause boredom in learning  figh among eleventh-grade-students at MAN Kota Solok. The purpose of this study was to determine : (1) students learning outcomes before the implementation of the Jigsaw learning model,( 2) student's learning outcomes after the implementation , and( 3)  the effect of the Jigsaw learning model on student's  fiqh learning outcomes . This study employe a quantitative approach with a quasi-experimental design using the one group Pretests-Posttest Design. The population consisted  of all eleventh-grade of MAN Kota Solok in the 2024/2025 academic year, while the sample was selected through Simple Random  Sampling, namely class XI IPK 2 at the experimental group. Data analysis using SPSS version 25 revealed that the average learning score increased  from 73,66 ( moderate category) before treatnent to 87,61 (high category) after applying the Jigsaw learning model. The t-test result showed a signifcan value of 0.000< 0.005 and count 6,131> t table 2.040 , indicating that Ha was accepted and H0 rejected. Therefore, it can be concluded that the Jigsaw learning model significantly improves studen's fiqh learning outcomes at MAN Kota Solok  Keywords : Jigsaw Learning Model, Learning Outcomes, Fiqh Learning